A Taxonomic Revision of the Orb Weaver Genus Acacesia (Araneae: Araneidae) - Susan Glueck (Psyche: A Journal of Entomology)
There are five species of Acacesia which range collectively from southern North America to Argentina. Two are previously known members of the genus. A. cornigera Petrunkevitch and A. hamata (Hentz). Three of these are new species: A. villalobosi and A. yacuiensis, fom southern Brazil, and A. benigna from Bolivia and Peru.